1998
DOI: 10.1021/ic971602v
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, X-ray Structure, Spectroscopic Characterization, and Theoretical Prediction of the Structure and Electronic Spectrum of Eu(btfa)3·bipy and an Assessment of the Effect of Fluorine as a β-Diketone Substituent on the Ligand−Metal Energy Transfer Process

Abstract: The 2,2'-dipyridyl adducts of two europium beta-diketonate complexes, Eu(btfa)(3).bipy [btfa = 4,4,4-trifluoro-1-phenyl-2,4-butanedione, bipy = 2,2'-dipyridyl] and Eu(bzac)(3).bipy [bzac = 1-phenyl-2,4-butanedione], have been prepared. The crystal structure of the former with chemical formula EuC(40)H(26)O(6)N(2)F(9) has been solved by single-crystal X-ray diffraction methods. The complex crystallizes in the monoclinic space group P2(1)/n with a = 11.122(5) Å, b = 22.860(8) Å, c = 15.870(6) Å, beta = 102.62(3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
42
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(47 citation statements)
references
References 27 publications
5
42
0
Order By: Relevance
“…More recently, extensive works have been carried out to comprehend the kinetic and thermochemical behaviors of β-diketone complexes and metallic β-diketone containing Ln 3+ ions [24,25]. Conventional isothermal experiments have appeared to be more commonly employed for those complexes because they are straightforward in opposition to nonisothermal procedures.…”
Section: Complexes Of General Formula [Eu(fod) 3 ·L] [Tb(fod) 3 ·L] mentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, extensive works have been carried out to comprehend the kinetic and thermochemical behaviors of β-diketone complexes and metallic β-diketone containing Ln 3+ ions [24,25]. Conventional isothermal experiments have appeared to be more commonly employed for those complexes because they are straightforward in opposition to nonisothermal procedures.…”
Section: Complexes Of General Formula [Eu(fod) 3 ·L] [Tb(fod) 3 ·L] mentioning
confidence: 99%
“…Recently, it has been found out that distinct luminescent properties of Ln 3+ ions could also be used for applications in biomedical [10,19], sensing [19,20] and optical imaging [14,21] due to their long-lived (milliseconds timescale) excited states. This had led to the most interesting developments in the coordination chemistry of Ln 3+ , and interests in its new applications are still emerging nowadays [22,23].More recently, extensive works have been carried out to comprehend the kinetic and thermochemical behaviors of β-diketone complexes and metallic β-diketone containing Ln 3+ ions [24,25]. Conventional isothermal experiments have appeared to be more commonly employed for those complexes because they are straightforward in opposition to nonisothermal procedures.…”
mentioning
confidence: 99%
“…In order to gain insight into the factors that determine the quantum yield and other relevant properties of lanthanide complexes our group has been investigating the photophysical properties of a number of new lanthanide complexes, using an approach based upon both theoretical and experimental work [8][9][10][11][12][13][14][15][16][17]. The results have shown that the quantum yield of a lanthanide complex arises from a balance among the rates of several processes, e.g., ligand to Ln 3+ energy transfer, multiphonon relaxation, energy back-transfer, crossover to charge-transfer states, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The results have shown that the quantum yield of a lanthanide complex arises from a balance among the rates of several processes, e.g., ligand to Ln 3+ energy transfer, multiphonon relaxation, energy back-transfer, crossover to charge-transfer states, etc. The control of these rates, as well as of other relevant physical properties, has been accomplished by a thorough selection of ligands, allowing us to develop some promising LCMDs [8,[11][12][13][14][15], with high quantum yields at room temperature, leading to new applications [6,7]. We are now reporting the synthesis, spectroscopic, X-ray characterization, and photophysical investigation, as well as the molecular and electronic structure prediction with emphasis on the ligand-centered triplet energy level of the lanthanide complexes Ln(tan) 3 …”
Section: Introductionmentioning
confidence: 99%
“…Usually, there are two types of lanthanide b-diketonates depending on whether the ratio of b-diketonate anion to lanthanide cation in the adducts is 3:1 (tris complexes) or 4:1 (tetrakis complexes) [3]. In particular, the tris complexes are most useful and extensively studied [4]. When three b-diketonates ''antenna" ligands chelated a trivalent lanthanide cation, the resultant complex is electrically neutral.…”
mentioning
confidence: 99%